Assessment of Yield, Flavonoid and Phytosterol Contents, and Fatty Acid Composition of Baru Almond Oil (Dipteryx alata Vogel) by Supercritical CO2 Extraction - Ferreira, Ana Carolina; Lopes, Guilherme [UNESP]; Filho, Antonio Carlos; Postaue, Najla; Belisário, Celso; Paim, Leonardo Lataro [UNESP]; Cardozo-Filho, Lúcio; da Silva, Camila; Ferreira-Pinto, Leandro [UNESP]; Favareto, Rogério (MDPI, 2024)
The objective of this study was to investigate the influence of temperature and pressure on the extraction of Baru almond oil using pressurized CO2. From the obtained data, it was found that variations in pressure and temperature influenced the oil yield and total amount of phytosterols. The maximum yield of Baru oil achieved was approximately 30%, obtained at a pressure of 28 MPa and 60 °C. The phytosterols identified were campesterol, stigmasterol, and β-sitosterol, with a maximum content of 169.5 ± 4.2 mg/100 g of oil obtained at 20 MPa and 60 °C. Among these, β-sitosterol was the most abundant, accounting for 60% of the total phytosterol content under all the experimental conditions. The flavonoid content in the extracts was also quantified, with the total flavonoid levels ranging between 255 and 275 mg/100 g of oil depending on the experimental conditions. The fatty acid profile of the extracted oil predominantly consisted of oleic (51%) and linoleic (28%) acids.
Keywords: Baru; flavonoids; supercritical extraction; β-sitosterol